2001
DOI: 10.1063/1.1381414
|View full text |Cite
|
Sign up to set email alerts
|

Tunable omnidirectional reflection bands and defect modes of a one-dimensional photonic band gap structure with liquid crystals

Abstract: We have theoretically investigated the tunability of the omnidirectional reflection band ͑ORB͒ of a one-dimensional ͑1D͒ photonic crystal ͑PC͒ consisting of alternating isotropic dielectric and nematic liquid crystal layers by an external electric field. The width of the ORB becomes wide as the external voltage increases, but the center frequency is changed little. The frequency of the defect mode created by inserting a layer of liquid crystals into a 1D dielectric PC is also found to be tunable by the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Recently, due to the realization of a metamaterial with negative refractive index (NRI) predicted by Veselago [17], defect layer using NRI materials are also available [18][19][20]. In addition, by making use of an electro-optical nonlinear defect, the device can become tunable [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, due to the realization of a metamaterial with negative refractive index (NRI) predicted by Veselago [17], defect layer using NRI materials are also available [18][19][20]. In addition, by making use of an electro-optical nonlinear defect, the device can become tunable [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For a 1D PC with alternating layers of Si and a nematic LC, Chigrin et al [17] showed that an applied voltage can produce switching of the transmitted light; this is realized due to the Freedericksz phase transition which consists in the alignment of the nematic LC molecules parallel to a (sufficiently large) electric field. For the same type or structure, Ha et al [18] demonstrated that it is possible to tune a complete PB gap-for both TE and TM polarizations. Bush and John [19] considered a synthetic inverse opal whose voids are infiltrated with a nematic LC.…”
Section: Introductionmentioning
confidence: 98%
“…Tuning of the ODR bands opens a means for control of the wave. 18 Although many models and approaches have been developed to study temperature effects of the band structure of PnCs, a similar study for the acoustic ODR bands, which would be of help in the design and optimization of thermal tuning of omnidirectional acoustic mirrors, has not been thoroughly investigated. Moreover, recent work has highlighted the potential of omnidirectional and tunable acoustic device using acoustic metamaterials.…”
mentioning
confidence: 99%